2006
DOI: 10.1515/sg-2006-0027
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Structure of The Wild Service Tree (Sorbus torminalis (L.) Crantz) in Poland

Abstract: Sorbus torminalis is a rare forest tree species in Poland. Allelic and genotypic structures at 25 isozyme gene loci were observed in 20 populations from Poland, situated mainly along a latitudinal gradient. Levels of genetic diversity were high both at the species level (P = 44 %, H e = 0.435) and within populations (mean P = 40.8 %, mean H e = 0.373). Levels of differentiation among populations were relatively high (F ST = 0.17) and a noticeable geographic structure of this differentiation was detected. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
16
3
Order By: Relevance
“…Kučerová et al (2010) found higher differentiation over central-European populations than those located in southern locations. Genetic differentiation among populations investigated in this study was found to be low, as compared to other studies (Demesure et al 2000, Bednorz et al 2006, Angelone et al 2007, Kučerová et al 2010, which might be attributed to close proximity of the populations under study. The FST and RST estimates were quite similar (FST = 0.048 ± 0.006 and RST = 0.059 ± 0.010), indicating that the differentiation was not caused by mutation, but rather it was due to specific colonization and gene flow patterns among populations (Balloux & Lugon-Moulin 2002).…”
Section: Iforest -Biogeosciences and Forestrycontrasting
confidence: 81%
See 1 more Smart Citation
“…Kučerová et al (2010) found higher differentiation over central-European populations than those located in southern locations. Genetic differentiation among populations investigated in this study was found to be low, as compared to other studies (Demesure et al 2000, Bednorz et al 2006, Angelone et al 2007, Kučerová et al 2010, which might be attributed to close proximity of the populations under study. The FST and RST estimates were quite similar (FST = 0.048 ± 0.006 and RST = 0.059 ± 0.010), indicating that the differentiation was not caused by mutation, but rather it was due to specific colonization and gene flow patterns among populations (Balloux & Lugon-Moulin 2002).…”
Section: Iforest -Biogeosciences and Forestrycontrasting
confidence: 81%
“…Inbreeding coefficients of S. torminalis are usually found to be slightly negative, indicating excess of heterozygotes as compared to expectations from Hardy-Weinberg equilibrium (Bednorz et al 2006). Our results confirmed this finding with inbreeding coefficients being consistently slightly negative across almost all SSR loci.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 95%
“…This value is similar to differentiation levels observed in studies based on allozymes (Bednorz et al 2006;Demesure et al 2000;Rasmussen & Kollmann 2007). Our observation is slightly higher, reflecting probably a larger area covered by sampling, as we investigated populations from south-eastern Europe and partly central Europe.…”
Section: Resultssupporting
confidence: 90%
“…Geographically proximate populations tend to be genetically more similar than expected under random distribution. This is partly contrasting with previous observations, since a strong isolation by distance was reported at the intrapopulation scale ), but at the regional scale, the observations differ: OddouMuratorio et al (2001) or Angelone et al (2007) identified only a weak IBD pattern, whereas Bednorz et al (2006) or Belletti et al (2008) found clear interregional differences. The observed patterns of geographical structure visible from model-based analysis may reflect glacial history and postglacial migration.…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation